2002
DOI: 10.1002/ijc.10311
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study evaluating the homogeneity and heterogeneity of risk factors between sinonasal and nasopharyngeal cancers

Abstract: Sinonasal cancer and nasopharyngeal cancer may share some risk factors because both are located within the upper aerodigestive tract. They may also have different etiological profiles because of anatomic or pathologic differences. However, the similarities and differences in risk factors have rarely been studied within the same population. We assessed the risk factor profiles of sinonasal and nasopharyngeal cancers, using data from a case-control study. The 2 case groups consisted of men aged 31-59 and diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
2
25
0
2
Order By: Relevance
“…Three studies reported an excess risk of NPC among printing workers (200,203,239), but did not identify specific inks, solvents, or other substances that could be responsible for the association. Although an excess risk of NPC has been observed among agricultural workers (38,186,232), studies assessing overall use of pesticides found no association with NPC risk (141,177,181,200).…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies reported an excess risk of NPC among printing workers (200,203,239), but did not identify specific inks, solvents, or other substances that could be responsible for the association. Although an excess risk of NPC has been observed among agricultural workers (38,186,232), studies assessing overall use of pesticides found no association with NPC risk (141,177,181,200).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The majority of casecontrol studies examining cigarette smoking and risk of NPC in a variety of populations reported an increased risk of 2-to 6-fold (9,39,40,73,142,(172)(173)(174)(175)(176)(177)(178)(179)(180)(181), establishing tobacco smoke as a consensus risk factor for NPC (182), although some studies found no association (24,38,74,137,141,148,154,(183)(184)(185)(186). Reports of a positive association between domestic exposure to secondhand smoke and risk of NPC (40,146,180) are likewise countered by studies with null findings (39,174).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational factors are responsible for a huge proportion of epithelial SNC besides other established congenital or acquired risk factors such as previous radiotherapy in the region and tobacco smoking (9) , chromosomal and genetically determined alterations (10,11) , inverted papilloma (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric and young adult patients lack the typical risk factors for sinonasal malignancies. 5 Young patients are also less likely to have significant comorbidities. So there remains a paucity of data to guide clinical decision making in young patients, particularly with respect to surgical management.…”
mentioning
confidence: 99%